Performance evaluation of a standalone solar PV system : a case study in Kendari, Southeast Sulawesi, Indonesia - Barata, La Ode Ahmad; Samhuddin, Samhuddin; Efendi, Rustam; Tando, Arjal (Jurnal Polimesin, 2025)
Rising energy demand and environmental concerns are driving efforts to find alternative energy sources. Photovoltaic (PV)-based power generation is a clean energy solution that continues to be developed for reliable energy supply. This study aimed to analyze global horizontal irradiance (GHI) and evaluate the performance of a PV-based power generation model in Southeast Sulawesi, Indonesia (latitude: -4.002°, longitude: 122.6°). The study was conducted from March to May 2024 using a commercial PV panel with a rated maximum power of 50 Wp. Instantaneous values of GHI, voltage, and electric current were recorded simultaneously. GHI data were closely related to the clearness index (Kt) and the diffuse fraction of solar irradiance. The highest hourly average GHI was observed in March, reaching 1.08 kW/m², while values in April and May ranged from 0.97 to 0.99 kW/m². The system achieved a daily average maximum power output of 34.53 watts and an instantaneous peak of 49.03 watts. The maximum daily efficiency, 12.48%, was recorded in May. Power conversion performance was found to correlate strongly with GHI and Kt values, with greater stability in these parameters leading to more effective energy harvesting. Additionally, solar energy was available for more than 8 hours per day under clear sky conditions during the transitional season. These empirical results provide new insights into PV performance in the region. However, long-term data collection and incorporation of temperature effects, especially in the dry season, will provide power reliability assessment and extend system usability in off-grid applications in the region.